FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA CAMAT DI KANTOR CAMAT KECAMATAN SARIO KOTA MANADO - UMASUGI, SARIWATI; LALOMA, ALDEN; Tampongangoy, Deysi Livi (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: This research moved from the fundamental problems, namely: the extent to whichemployees of the Performance Role Head office Head Sario Manado city districts. Thus, this studyaims: to know the effect on the Role of Employee Performance Head Head office Sario Manado citydistricts. This study uses a quantitative approach to the application of descriptive and explanatory.Data and information collected through a technical questionnaire distributed to 26 respondents, andequipped with observation and interview techniques (Interview), then analyzed by applying thetechniques of frequency table analysis, product moment correlation and simple linear regression.Based on the analysis, it is known that: a descriptive analysis results through analysistechnique table (frequency table) it is known that the distribution of respondents to variable EmployeeRole in the category "medium" to "low", but dominant categorized "medium" or medium with themean average performance of 60.57%, while the Employee performance varies from moderate to high,but tends to be in the category of "moderate" with an average performance of 66.15%.Thus, it can be concluded that the role of employee positive and significant impact onperformance and be contributive Head. This means that empirically Role of Employees contributesignificantly and substantially to the Head of Performance, particularly the sub-district office SarioManado city districts.Keywords: The role of employees, Head of Performance